Contrastive Research of College Students’ English Learning Methods Based on Internet and Traditional Environment - Li , Zhenying; Honghong, Mo (Advances in Social Sciences Research Journal, 2020)
Before the popularity of smart phone, traditional English learning way was chosen by a lot of students. Traditional English learning way made the study more difficult for many students, and resulting in non-active study phenomenon. In recent years, with the help of smart phone APP, the quality and ability of students’ learning have been generally improved. It dramatically improves student’s learning interest. The rapid emerging of Internet Technology in China provides tremendous development space for virtual learning. At the same time, it also launches enormous challenge to traditional learning way. Traditional learning way suffers unprecedented crisis, however, virtual learning way which from being questioned, there are inevitability and value of virtual learning which people begin to think about. In order to deal with the new situation, this paper outlines the online learning method and the traditional learning method respectively through comparative analysis. Through the literature review method to search the relevant references, the information obtained is integrated and summarized, the existing problems of network learning methods and traditional learning methods are analyzed. We can further put forward rational suggestions for future development.